Outdoor physical activities in physical education and sports at the Beni Mellal Provincial Directorate - Mohamed BOUKHALKHAL; Youssef SIAME; Abderrahim RHARIB (African Scientific Journal, 2025)
Abstract Through this study, we determine the interest allocated to physical outdoor activities on the part of teachers and students. As a realization of this study, we registered in constructivism, and we used questionnaires and interviews. Questionnaires were sent to the students, while interviews were held with PES teachers of Beni Mellal provincial direction. Physical Outdoor Activities (POA) can be qualified as physical and sports activities (PSA) that can promote self-construction of knowledge, skills development and education of individuals to the values of life, of citizenship and of the environment. Thanks to the pedagogical and socioeconomic interests of the OPAs, the teachers of the PES and their pupils express a great wish for their integration in the PES curriculum. Sport in Moroccan schools can be found in two complementary forms: Physical Education and Sports (PES) and the School Sports Association (SSA). The PES is a teaching material, where the legislator has underlined a set of educational objectives and skills that are transmittable to the socio-professional life of learners, while the SSA represents a field of blossoming and sporting development. Despite the sports orientation of the SSA, the two entities, PES and its subsidiary ASS, work in synergy to train a citizen fit to integrate into society. Optimization of the achievement of this goal can be achieved through the introduction of new forms of school sports practices. Keywords: School sport tourism, POA, Interest, Nature, Environment.